ANALYSIS OF THE USE CRAFTS IN THE EDUCATIONAL AREA HUMANS AND THE WORLD OF WORK - MANĚNOVÁ, Martina; TRPKOVÁ, Pavlína (Trends in education, 2010)
The paper presents a survey of the use of crafts in the educational area Humans and the world of work. This survey showed that the crafts are more reli-teaching in village schools, teachers draw the most from books and magazines and the trades are classified mainly in connection with the traditional festivals.
Keywords: Human and the Word of work; crafts; tradition